2018
DOI: 10.1515/sjpain-2018-0041
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing risk of spinal haematoma from spinal and epidural pain procedures

Abstract: Abstract Background and aims: Central neuraxial blocks (CNB: epidural, spinal and their combinations) and other spinal pain procedures can cause serious harm to the spinal cord in patients on antihaemostatic drugs or who have other risk-factors for bleeding in the spinal canal. The purpose of this narrative review is to provide a practise advisory on how to reduce risk of spinal cord injury fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 98 publications
(234 reference statements)
0
43
0
Order By: Relevance
“…Based on published guidelines, derived by clinical case reports and consensus, a large subset of clinicians report stopping antiplatelet therapy and consider this concept as a standard of care (1,20,33,(36)(37)(38)(122)(123)(124)(125)(126)(127)(128)(129). Although the overall incidence of bleeding complications and epidural hematoma in the non-obstetric epidural literature has been reduced, the incidence has been higher with procedures involving cervical and thoracic spine (1,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(52)(53)(54)129). Of note, the clinical literature reports of incidences of epidural hematoma cases accompanying interventional techniques and neuraxial techniques are increasing rapidly (1,20,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on published guidelines, derived by clinical case reports and consensus, a large subset of clinicians report stopping antiplatelet therapy and consider this concept as a standard of care (1,20,33,(36)(37)(38)(122)(123)(124)(125)(126)(127)(128)(129). Although the overall incidence of bleeding complications and epidural hematoma in the non-obstetric epidural literature has been reduced, the incidence has been higher with procedures involving cervical and thoracic spine (1,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(52)(53)(54)129). Of note, the clinical literature reports of incidences of epidural hematoma cases accompanying interventional techniques and neuraxial techniques are increasing rapidly (1,20,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall incidence of bleeding complications and epidural hematoma in the non-obstetric epidural literature has been reduced, the incidence has been higher with procedures involving cervical and thoracic spine (1,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(52)(53)(54)129). Of note, the clinical literature reports of incidences of epidural hematoma cases accompanying interventional techniques and neuraxial techniques are increasing rapidly (1,20,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another single‐centre study, identified zero spinal haematomas and abscesses in 3035 postoperative patients treated with epidural analgesia for a mean duration of 2.1 catheter days from 2008 to 2013 . Historically, the incidence of serious complications after epidural analgesia has been considered to be extremely low, but nowadays it is accepted that the incidence may range from 1:6000 to 1:1000 epidural procedures depending on patient‐related risk factors, such as antihaemostatic medication use and anatomy of the spinal column . The aim of this survey was to quantify trends in practice of epidural analgesia and to assess the extent to which epidural alert systems for neurological complications of epidural analgesia have been introduced in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The 3rd UK National Audit Project (NAP 3) recorded no cases of vertebral canal haematoma among 365,000 spinal anaesthetics. The risk may be slightly increased in older patients with hepatic/renal impairment, spinal deformity and those undergoing repeated attempts at spinal needle insertion , but the Association of Anaesthetists recommends that such cases should be attended to by ‘experienced’ clinicians to minimise this risk .…”
mentioning
confidence: 99%